Kedudukan Pemeriksaan Substantif Terhadap Keabsahan Sertifikat Merek - Tonni Daniel Hutabarat; Abdul Lawali Hasibuan; Dessy Agustina Harahap (JUNCTO: Jurnal Ilmiah Hukum, 2021)
This writing aims to determine the function of trademark registration and to prevent the occurrence of a similarity in the type of mark on a product and to determine the position of a substantive examination of the validity of a trademark certificate based on the prevailing laws and regulations in Indonesia. This research is a descriptive normative legal research with an empirical juridical approach. The data source of this research comes from primary data in the form of interviews with judges at the Medan District Court, and secondary data consisting of primary, secondary, and tertiary law. Data collection tools are carried out by documentation study or literature study. The analysis technique used in this research is qualitative data analysis. Regulations on trademark law, intellectual property rights in a substantive examination of the validity of a trademark certificate are regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications which are part of signs in the form of images, names, words, letters, numbers, and composition. color or the distinction used in trade in goods or services. A mark is an exclusive right granted by the state to a party that has registered a mark with the Directorate General of IPR.